Job Satisfaction Levels and Contributing Factors Among Health Professionals in Rural Public Healthcare Facilities of Limpopo Province, South Africa - Nkobeni, Maseeng Lydia; Mukonza, Ricky Munyaradzi; Mokoena, Oratilwe Penwell; Ntuli, Sam Thembelihle (Program Studi Kesehatan Masyarakat UIN Alauddin Makassar, 2024)
Job satisfaction reflects an employee's motivation and contentment with their work. Globally, the turnover and retention of healthcare professionals are essential for providing vital health services. However, there has been minimal research on job satisfaction among healthcare professionals in rural areas of South Africa. This study aimed to evaluate job satisfaction and its contributing factors among healthcare professionals in the rural provinces of South Africa. A cross-sectional study was conducted, involving nurses and medical doctors across four public healthcare facilities over a three-month period. Out of 84 questionnaires distributed, 83 were completed, yielding a response rate of 98.8%. Overall, 37.3% of participants expressed satisfaction with their job. The main factors contributing to dissatisfaction were a lack of resources (81%), subpar working conditions (80%), inadequate rewards for extra efforts (75%), and a high workload (73%). The findings revealed notably low job satisfaction, underscoring the need for strategic planning and effective human resource management. Enhancing job security, improving working conditions, offering fair compensation, and supporting career advancement are essential. Addressing workload management through optimized schedules, reduced turnover, skilled recruitment, and task prioritization training is also recommended.